Providing care to patients with COVID-19 in a reference hospital: health care staff intentional behavior and factors that affect it Running title: Intention to provide care to COVID-19 patients - Theodoros Pesiridis; Petros Galanis; Eleni Anagnostopoulou; Athena Kalokerinou; Panayota Sourtzi (AIMS Press, 2021)
Objective: The investigation of intentional behavior of hospital staff to care for COVID-19 patients and the study of the factors that influences it. Method: This is a cross-sectional study, of 261 physicians and nurses working in a COVID-19 reference hospital. Data were collected by an anonymous questionnaire including demographic and professional characteristics and a scale measuring behavioral intention based on the Theory of Planned Behavior of Ajzen. Statistical analysis was performed by SPSS 21. Results: Mean age of participants was 40.8 years old, while most of them were nurses (75.7%). Behavioral intention mean score was 18.2 (5-21), which shows high intention to care for COVID-19 patients. Bivariate analysis between independent variables showed that behavioral intention mean score was higher for those that had cared for COVID-19 patients and those that did not (19.0% vs. 16.7%, p < 0.001). Multivariate linear regression analysis identified that increased subjective norms (the perceived social pressure to perform or not the behavior) score was associated with increased behavioral intention score (p < 0.001). Also, participants that provided care for COVID-19 patients had higher behavioral intention score (p < 0.001). Conclusion: Healthcare staff, that cared for COVID-19 patients had high behavioral intention to continue caring for them. This finding could be used to inform policies and training for staff that will be employed in COVID-19 units.